Microsatellite identification and characterization in peanut (A. hypogaea L.) - Ferguson, Morag E.; Burow, Mark D; Schulze, S.R.; Bramel-Cox, P.J.; Paterson, A.H.; Kresovich, Stephen; Mitchell, S. (Springer, 2004)
A major constraint to the application of biotechnology to the improvement of the allotetraploid peanut, or groundnut (Arachis hypogaea L.), has been the paucity of polymorphism among germplasm lines using biochemical (seed proteins, isozymes) and DNA markers (RFLPs and RAPDs). Six sequence-tagged microsatellite (STMS) markers were previously available that revealed polymorphism in cultivated peanut. Here, we identify and characterize 110 STMS markers that reveal genetic variation in a diverse array of 24 peanut landraces. The simple-sequence repeats (SSRs) were identified with a probe of two 27,648-clone genomic libraries: one constructed using PstI and the other using Sau3AI/BamHI. The most frequent, repeat motifs identified were ATT and GA, which represented 29% and 28%, respectively, of all SSRs identified. These were followed by AT, CTT, and GT. Of the amplifiable primers, 81% of ATT and 70.8% of GA repeats were polymorphic in the cultivated peanut test array. The repeat motif AT showed the maximum number of alleles per locus (5.7). Motifs ATT, GT, and GA had a mean number of alleles per locus of 4.8, 3.8, and 3.6, respectively. The high mean number of alleles per polymorphic locus, combined with their relative frequency in the genome and amenability to probing, make ATT and GA the most useful and appropriate motifs to target to generate further SSR markers for peanut.